"Tihi ton" estetike umetnostne religije - Barbo, Matjaž (Primerjalna književnost, 2015)
The article presents an analysis of the juncture of music and literature, especially in the work of Robert Schumann. It touches upon the meaning of music as a declaration of an elevated mission of art, which can be apprehended only by a sensitive listener. It is to such a listener alone that the transcendental vastness of the artistic meta-world - enabled by the amalgamation of the arts into an integrated totality - becomes accessible.
Keywords: Schumann, Robert, 1810-1856; književnost in glasba; umetnostna religija; semantika glasbe; glasbena hermenevtika; moto